2022
DOI: 10.1109/tvcg.2022.3209448
|View full text |Cite
|
Sign up to set email alerts
|

Dashboard Design Patterns

Abstract: How to cite:Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…This design divergence served to simplify the visual interface by using two distinct visual components (in version 1) instead of one (in version 2) to present the same information, thereby aiding teachers with low VL to comprehend the data. This aligns with dashboard design patterns that advocate not posing too many questions for a single graph (Bach et al, 2022). On the other hand, for teachers with high VL, DS had a lesser impact on their cognitive load when using different dashboards.…”
Section: Summary Of Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…This design divergence served to simplify the visual interface by using two distinct visual components (in version 1) instead of one (in version 2) to present the same information, thereby aiding teachers with low VL to comprehend the data. This aligns with dashboard design patterns that advocate not posing too many questions for a single graph (Bach et al, 2022). On the other hand, for teachers with high VL, DS had a lesser impact on their cognitive load when using different dashboards.…”
Section: Summary Of Resultssupporting
confidence: 73%
“…Two additional dashboard prototypes, which included DS elements, were created as a part of a codesign process described by Pozdniakov et al (2022). Based on information visualisation principles (Bach et al, 2022), in all three dashboards, a timeline chart is included at the top as a frame of reference indicating the activity in which the class is currently located (see Timeline in Figures 1, 2 and 3, which contains three activities along with the start and final times of the class. In these figures, the current activity selected by the teacher is highlighted in navy blue over grey, as shown with Activity 3).…”
Section: Contextmentioning
confidence: 99%
“…In a 2020 paper for example, dashboards were shown to be effective in providing interactive visualizations to support clinical or managerial purposes in the hospital ( 38 ). In three recent papers published in 2021 ( 39 ) and 2022 ( 40 , 41 ), different design patterns and frameworks for dashboards were proposed but none included PM approaches for oncology. The only project found that included interactive dashboards with PM algorithms was published in 2019 and was intended to analyze processes in surgical rooms ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Demonstrating the value of data through an online dashboard offers several benefits for organizations, stakeholders, and users. Online dashboards offer the ability to make information accessible to users in a variety of domains (Bach et al, 2022). These dashboards are powerful tools that provide a visual representation of data, making complex information more accessible, understandable, and actionable.…”
Section: Dashboardsmentioning
confidence: 99%